Dysfunction of RAB39B‐Mediated Vesicular Trafficking in Lewy Body Diseases. Issue 8 (3rd May 2021) - Koss, David J.; Campesan, Susanna; Giorgini, Flaviano; Outeiro, Tiago F.
Abstract: Intracellular vesicular trafficking is essential for neuronal development, function, and homeostasis and serves to process, direct, and sort proteins, lipids, and other cargo throughout the cell. This intricate system of membrane trafficking between different compartments is tightly orchestrated by Ras analog in brain (RAB) GTPases and their effectors. Of the 66 members of the RAB family in humans, many have been implicated in neurodegenerative diseases and impairment of their functions contributes to cellular stress, protein aggregation, and death. Critically, RAB39B loss‐of‐function mutations are known to be associated with X‐linked intellectual disability and with rare early‐onset Parkinson's disease. Moreover, recent studies have highlighted altered RAB39B expression in idiopathic cases of several Lewy body diseases (LBDs). This review contextualizes the role of RAB proteins in LBDs and highlights the consequences of RAB39B impairment in terms of endosomal trafficking, neurite outgrowth, synaptic maturation, autophagy, as well as alpha‐synuclein homeostasis. Additionally, the potential for therapeutic intervention is examined via a discussion of the recent progress towards the development of specific RAB modulators. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : August Infographic: Dysfunction of RAB39B‐Mediated Vesicular Trafficking in Lewy Body Diseases